Picoperovskites: the smallest conceivable isolated halide perovskite structures formed within carbon nanotubes - Kashtiban, RJ; Patrick, CE; Ramasse, Q; Walton, RI; Sloan, J (Wiley, 2023)
Halide perovskite structures are revolutionizing the design of optoelectronic materials, including solar cells, light-emitting diodes, and photovoltaics when formed at the quantum scale. Four isolated sub-nanometer, or picoscale, halide perovskite structures formed inside ≈1.2–1.6 nm single-walled carbon nanotubes (SWCNTs) by melt insertion from CsPbBr3 and lead-free CsSnI3 are reported. Three directly relate to the ABX3 perovskite archetype while a fourth is a perovskite-like lamellar structure with alternating Cs4 and polyhedral Sn4Ix layers. In ≈1.4 nm-diameter SWCNTs, CsPbBr3 forms Cs3PbIIBr5 nanowires, one ABX3 unit cell in cross section with the Pb2+ oxidation state maintained by ordered Cs+ vacancies. Within ≈1.2 nm-diameter SWCNTs, CsPbBr3 and CsSnI3 form inorganic-polymer-like bilayer structures, one-fourth of an ABX3 unit cell in cross section with systematically reproduced ABX3 stoichiometry. Producing these smallest halide perovskite structures at their absolute synthetic cross-sectional limit enables quantum confinement effects with first-principles calculations demonstrating bandgap widening compared to corresponding bulk structural forms.